Clinical features of different types of the eye trauma and its outcomes in children (Ukrainian Journal of Ophthalmology, 2026)
Purpose: The study aimed to determine the clinical features of the eye trauma and its outcomes in children in Ukraine.Methods: The features of the clinical picture of different types of eye trauma, methods of treatment and consequences are analyzed.Results: Pediatric eye trauma is characterized by a predominance - 63.4% of OGIs with damage to 3 or more structures of the eye in 88.4% of cases, the highest frequency of injury to the lens (73.1%), in 61.6% of cases with the presence of foreign bodies and in 50% there was a combination of open and closed damage to the eyeball. Conclusion: Clinical features of pediatric eye trauma require differentiated clinical tactics including surgical and conservative methods. Reconstructive surgical rehabilitation including complex procedures with maximum restoration of all injured structures with IOL implantation using advanced technologies combined with conservative treatment allow to restore high visual acuity (0.3 and higher) in 64.3% of cases of the explosive injury in follow up terms.
Keywords: оcular injury; treatment; outcomes; children